2016
DOI: 10.1038/jhg.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies. Patients with PDAC are often asymptomatic, and many have lymph node and distant metastases as well as vessel invasion upon diagnosis. Surgery and current chemotherapy have limited efficacy for improving prognosis, which accounts for overall median survival of 8.6 months and a 9.7% 5-year survival rate. MicroRNAs (miRNAs) are attracting increasing attention because of their association with tumour progression. At least 50% of miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 128 publications
3
130
0
2
Order By: Relevance
“…This panel was designed and validated with the intent to be incorporated into the routine clinical testing. Table 1 not only summarizes the role and biological function of each miRNA present in this panel but also describes their clinical relevance [16,33,34,42,43]. miRNA is obtained using the miRNeasy FFPE Kit (Qiagen, Hilden, Germany), and it requires four to six FFPE (formalin-fixed, paraffin-embedded) unstained slides of 5 μm each.…”
Section: Mirna and Pancreatic Diseases: The Dartmouth-hitchcock Medicmentioning
confidence: 99%
“…This panel was designed and validated with the intent to be incorporated into the routine clinical testing. Table 1 not only summarizes the role and biological function of each miRNA present in this panel but also describes their clinical relevance [16,33,34,42,43]. miRNA is obtained using the miRNeasy FFPE Kit (Qiagen, Hilden, Germany), and it requires four to six FFPE (formalin-fixed, paraffin-embedded) unstained slides of 5 μm each.…”
Section: Mirna and Pancreatic Diseases: The Dartmouth-hitchcock Medicmentioning
confidence: 99%
“…All these modes of actions constitute a complicated, multi-node and multi-layer regulatory network. In addition to its normal functions, assembling evidences suggest that miRNA are also involved in various pathological conditions such as cardiomyopathies [8], atherosclerosis [9], obesity [10] and cancer [11]. Most importantly, emerging evidences suggest that miRNAs play crucial roles in inflammation responses [12], as well as in acute lung injury and ARDS [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent requirement for novel therapeutic treatments for patients with pancreatic cancer. A number of studies have indicated that miRNAs contribute to the carcinogenesis and progression of numerous types of human cancer via targeting multiple mRNAs (22)(23)(24). Therefore, identification of specific miRNAs may provide therapeutic implications and may be exploited to improve treatments for patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%